The Impacts of Assessment Modes and Personality Traits on Speaking Skills Development in Iranian EFL Learners Across Proficiency Levels - Safarpour , Samaneh; Mashhadi Heidar, Davood; Rahimy, Ramin (Assessment and Practice in Educational Sciences, 2026)
This study investigates the effects of face-to-face group dynamic assessment (FTF-GDA) versus web-based group dynamic assessment (WB-GDA) on speaking proficiency among Iranian EFL learners, considering personality traits and proficiency levels. Grounded in Vygotsky’s sociocultural theory, a quantitative quasi-experimental design with pretest-posttest was employed, involving 170 learners (ages 16–18) selected via convenience sampling from Ariana Institutes in Rasht. Participants were divided into 12 experimental and 6 conventional groups, undergoing 15 treatment sessions with evaluations pre- and post-intervention. Analysis through three-way ANOVA indicated significant improvements in speaking proficiency for all groups. FTF-GDA particularly benefitted extroverted beginners, enhancing interactive dynamics, while WB-GDA suited introverted advanced learners by providing a self-paced environment. Conventional methods resulted in minor progress, notably among intermediate extroverts. These findings underscore the necessity of adapting dynamic assessment strategies to align with diverse learner profiles to enhance speaking proficiency, suggesting FTF for extroverted beginners and WB for introverted advanced learners. Pedagogically, EFL instructors should tailor GDA modalities—FTF for extroverted beginners and WB for introverted advanced learners—to optimize speaking proficiency based on personality and proficiency levels.